GAMBARAN ADAPTASI REPRODUKSI BREED KAMBING BOER DAN BOERAWA SEBAGAI PEMACEK PADA KAMBING LOKAL DI SULAWESI TENGAH - Mirajuddin Mirajuddin (Agroland: Jurnal Ilmu-ilmu Pertanian, 2006)
A’true experiment’ research on Boer and Boerawa goats reproductive ability for improving local goat genetic through Artifian Insemination (AI) was conducted at a village farm in Wani I, Kayu Malue, Palu Utara, Donggala district, Central Sulawesi from March to Desember 2002.  This study aims at improving the genetic and production of Palu local goat by improving their reproductive efficencies. A “true experimental design” was applied in which the reproductive ability of male goat from two different breeds was tested on female local goat through AI.  Descriptive analysis of semen and spermatozoa qualities showed that Boerawa breed had higher semen quality (D/+++/90%) than male Boer (SD/++/75%).  Proporsional statistical analysis indicated that Conception Rate (CR) of female local goat that was artificially inseminated with Boerawa semen (CR : 100%) was significantly higher (P<0.05) than those of female local goat inseminated with Boer semen  (CR : 60%). Considering the importance of improving the production and productivity of local goat in Central Sulawesi through improving reproductive efficiency, basic or applicative experiments on the reproductive adaptation of high production breeds to improve genetic potential of local breed are continuosly needed.